Creating Corporate Accountability: Foundational Principles to Make Corporate Citizenship Real - Waddock, Sandra (Journal of business ethics, 2004)
This paper explores the growing array of initiatives aimed at creating corporate accountability with the goal of attempting to uncover the foundation principles that underlie them and create a “floor” below which practices are ethically questionable. Using the Global Compact's nine principles and the work of Transparency International as guides, foundational principles seem to exist in the areas of human rights, labor standards, environment, and anti-corruption initiatives.